RELEVANCE OF GURU NANAK’S CURRENT TEACHINGS - Dr. Vedant Sharma (International Scientific and Current Research Conferences, 2023)
Guru Nanak, the incredible defender of fifteenth century humanism at the auditorium of Indian history, is seen as an best of frequent agreement. He gave as lengthy as he can take into account to advancing amicability amongst folks of quite a number religions. In distinction to a preferred man, from his childhood, Nanak began to song down a extraordinary approach of spanning the holes between the real value of existence and the devotees of a number of religions. His classes shape the storm cellar of Sikhism and he is seen as the predominant Guru of the Sikh strict custom. The integral goal of Guru Nanak's classes can be supposed to be an undertaking to construct up world concord by using ending mutual struggles. An errand that he, when all is stated and done, wished to end for the period of his life. Through this article an recreation has been made to find out the pertinence of the instructions of Guru Nanak Dev Ji which can direct closer to an amicable society.